Lessons from innovation in medical education during the COVID-19 pandemic: student perspectives on distributed training - Ruhann Botha; Danyca Breedt; Dylan Barnard; Ian Couper (James Cook University, 2023)
Introduction: Can the forced adaptation brought about by COVID-19 inform the future of clinical education? This study brings a low- and middle-income country perspective to this question. Most studies of the impact of COVID-19 on medical students' training have been conducted in high-income countries, where the infrastructure to convert to alternative virtual or COVID-19-friendly training platforms (online teaching or case discussions and skill development centres) is more established than in low- and middle-income countries. In South Africa, Stellenbosch University instead chose to move substantial components of clinical training away from the traditional city tertiary campus and into smaller district hospitals. The main objective of this study was to ascertain the perspectives of these student interns regarding the quality of their restructured training at distributed health facilities during the COVID-19 pandemic and compare the perspectives of rural-site students with those of metropolitan (metro)-site students. Methods: A cross-sectional study was conducted by REDCap survey. Quantitative data were analysed by SPSS Statistics by doing descriptive and inferential statistics. The statistical significance of associations was determined by a p-value of <0.05. Likert-scale questions were analysed as ordinal variables to determine distribution of the responses, and non-parametric Mann-Whitney tests were used to compare distributions between rural and metro groups. Qualitative questions were analysed thematically by identifying common themes. Ethical approval was obtained for the study. Results: There were 155 respondents (62% response rate). Although 74.6% of participants indicated that they developed approaches to undifferentiated problems and illnesses, rural-site students were more likely to perceive that they learnt new procedures (p=0.006) and improved their ability to perform procedures previously learnt (p=0.002) compared to metro-site students. Rural-site students reported that they saw more patients independently than during previous training (p<0.001) and felt that they took more responsibility for patient management (p<0.001) than metro-site students. Students at rural sites were more likely to agree that training during the pandemic provided good learning opportunities (p<0.001) and that medical students form a necessary part of the pandemic response. Overall, students at both distributed sites felt that their training gave them more confidence for their future internship than previous training at central teaching hospitals (median=2 (agree)). Conclusion: The COVID-19 pandemic provided challenges for the continuation of quality medical training. It also provided the opportunity for innovative changes. This study demonstrates the successful outcomes, even during the pandemic, of distributed-site training, where students are immersed in the healthcare team, take responsibility of patient management and report that they improve their skills. Students at rural sites tended to report a more positive perspective on their clinical training. Rather than seeing the end of the pandemic as a time to revert to the previous status quo, the students in this study suggest to us that the lessons learnt from this forced innovation in distributed learning can now inform a better approach to clinical education for the future.